Keragaman Morfologi Kerang Hotate (Patinopecten yessoensis) di Teluk Funka Hokkaido Jepang - Aulya, Aisyah Safna; Sanjayasari, Dyahruri; Muslih, Muslih (MAIYAH, 2023)
Hotate scallop are cold water species that can only be cultivated in cold waters. Consumption of Patinopecten yessoensis, Jay 1857 from Japan and other countries shows greater demand, so research related to hotate scallop is important to manage hotate culture and its broodstock to maintain continous supply of this marine product. The purpose of this study is to determine the similarities and dissimilarities morphological characters of hotate scallop in Funka Bay Japan based on landmark characteristics. Data collection technique used was purposive sampling. Morphological measurements was conducted using Image-J software, principle component analysis using PAST software. The results indicate that the level of similarity of hotate scallop in cluster I is 70% and in cluster II is 85%. The principal components of hotate scallop morphometric landmarks is growth line number A20, A21, A22, A23, A25 from total 35 landmarks.